SEJARAH DAN PERUBAHAN, PERKEMBANGAN PENDIDIKAN ISLAM DI MESIR - Delisa, Delisa; Sari Rohati (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Educational reform in Egypt has become a major focus of the government and society, especially in recent decades. Various initiatives have been launched to improve the quality of education, following global trends in the development of more relevant and effective education systems. The education system in Egypt consists of several levels, starting from primary education, secondary education, to tertiary education. Education management in Egypt involves a series of policies, programs, and practices designed to manage and coordinate various aspects of education in the country. Overall, educational management in Egypt covers various aspects designed to ensure effective and efficient management of the national education system in order to achieve stated educational goals. Educational reform in Egypt is an effort aimed at restructuring and improving the education system in the country. These reforms are driven by awareness of the need to improve the quality of education, overcome existing challenges, and prepare Egypt's young generation to face global changes and the demands of an increasingly complex job market.